Indoxyl Sulphate is Associated with Atrial Fibrillation Recurrence after Catheter Ablation. Issue 1 (December 2018) - Yamagami, Fumi; Tajiri, Kazuko; Doki, Kosuke; Hattori, Masayuki; Honda, Junya; Aita, Satoshi; Harunari, Tomohiko; Yamasaki, Hiro; Murakoshi, Nobuyuki; Sekiguchi, Yukio; Homma, Masato; Takahashi, Naohiko; et al.
Abstract Renal dysfunction results in the accumulation of various uremic toxins, including indoxyl sulphate (IS), and is a major risk factor for atrial fibrillation (AF). Experimental studies have demonstrated that IS exacerbates atrial remodelling via oxidative stress, inflammation, and fibrosis. However, its clinical impact on AF-promoting cardiac remodelling has not been described. Therefore, the purpose of this study was to clarify the relationship between basal IS levels and the 1-year outcomes after catheter ablation for the treatment of AF. Our prospective observational study included data from 125 patients with AF who underwent catheter ablation. Over a 1-year follow-up period, AF recurrence was identified in 21 patients. The 1-year AF-free survival was significantly lower in patients with high serum IS levels (≥0.65 μg/mL) than in those with low IS levels (60.1 ± 10.4%versus 85.2 ± 3.9%, P = 0.007). Univariable analysis identified that an IS concentration ≥ 0.65 μg/mL was associated with AF recurrence (hazard ratio [HR] = 3.10 [1.26–7.32], P = 0.015), and this association was maintained in multivariate analysis (HR = 3.67 [1.13–11.7], P = 0.031). Thus, in patients undergoing AF ablation, serum IS levels at baseline independently predict the recurrence of arrhythmia.